The Symmetry In Kinematics Between The Dominant And Non-Dominant Legs In Taekwondo Turning Kick - Harun , Hafizah; Siau , Jun Xiong (2010)
The objective of this study was to determine the differences between dominant and non-dominant leg in Taekwondo Turning Kick. There were 5 subjects who are Johor state national level black belt Taekwondo players with the mean age 21.71 ± 2.58 years old, mean weight 55.87 ± 6.76 kg and mean height 170.22 ± 5.41 cm. This research was carried out in the XF Dance and Martial Arts Studio, located in Bandar Putra, Kulai, Johor. A Sony DCR-HC38 digital video camera with 25 frames per second (fps) was used for the sagittal view recording. Movements analysis software - SiliconCoach 7 were used in the digitizing process, which were done manually with a reference point marked at the tarsal bone. The results were focused, firstly, on the comparison of the dominant and non-dominant kicking speeds and secondly, the relationship between the vertical kicking angle and the maximum height at the target spot. The results showed that mean peak velocity for the dominant and non-dominant kick were 12.93 m/s and 12.27 m/s respectively. T-test showed that there were no significant differences in velocity between dominant and non-dominant legs in Taekwondo turning kick. Therefore the null hypothesis of this research was achieved. The mean dominant vertical angle was lower than the mean non-dominant angle which were 70.62° and 72.68° respectively, whereas the mean height of the kick by dominant leg was higher than mean height of the kick by non-dominant leg (1.23m and 1.20m respectively). In conclusion, the expert Taekwondo players were equally fast and efficient during the turning kick when using both dominant and non-dominant legs.